A survey of transfer pricing practices of companies in selected industries on Bursa Malaysia / Aliza Ramli, Shelia Christabel and Prof Madya Teh Khuan Ying - Ramli, Aliza; Christabel, Shelia; Teh, Khuan Ying (2005)
This paper is basically a survey of the transfer pricing practices of firms in selected industries on Bursa Malaysia. In our survey, we have looked at the transfer price methods that are commonly used by firms. It also looked into the important factors that influence the design and operation of the transfer pricing system and if there are any differences between firms size and age and between service and non-service industries. The results showed that the popular methods used are the actual cost to produce and process goods and/or services to the point of transfer and external market price of similar competing goods. Majority of the firms that did not practice transfer pricing gave insignificant volume of interdivisional transfer in the firm, as their reason. This is in line with the study conducted by McGaughey (1997). Majority of the firms in the survey stated that their transfer pricing methods are similar to other firms. Return on investment, profit and firm's growth and taxes are the important factors considered by firms in establishing transfer prices. The findings indicated the overall importance of transfer pricing objectives of firms is not associated with firm's size and age. Overall, there is no significant relationship between the extent of managers' involvement at various levels with size and age of firms and whether it is a service or non-service firm.